Gambaran Perilaku pada Pasien Penyakit Tidak Menular di Puskesmas Putri Ayu - Yuliana, Yuliana; Nurfitriani, Nurfitriani; Al Fajri, Jufri (3031-8572, 2024)
Non-communicable diseases (NCDs) are known as chronic diseases but are not transmitted from person to person. The World Health Organization (WHO) predicts that in 2020 non-communicable diseases will be the cause of 73% of deaths in the world (Isa, 2017). Non-communicable diseases consist of asthma, chronic obstructive pulmonary disease (COPD), cancer, diabetes mellitus (DM), hyperthyroidism, hypertension, coronary heart disease (CHD), heart failure, stroke, chronic kidney disease, kidney stones and joint disease or rheumatism. Around 80% of all NCD deaths occur in low-income countries (Riau Provincial Health Office, 2019). Some factors that trigger non-communicable diseases are behavioral factors such as smoking, alcohol consumption, lack of physical activity, fast food, lack of fruit and vegetable consumption, this is certainly a trigger for a person's physiological health. The study was conducted to see the Behavioral Description of Non-Communicable Disease (NCD) Sufferers at the Putri Ayu Health Center in Jambi City in 2023/2024. The research design used was descriptive with univariate data analysis with a sample of 25 respondents using a purposive sampling technique. The study was conducted from October 2023 to August 2024. The results of the study showed that 60% of respondents were not at risk, 56% did not carry out disease prevention, 100% of respondents did not carry out disease screening, 96% of respondents carried out disease control. For the Putri Ayu Health Center, it can provide education to NCD sufferers in the form of prevention and control of NCD diseases